The Relative Bandwidth Occupation Ratio Event Triggered Control on Power System With LFC-VSG Scheme under Unreliable Network - Shao, Yingying (International Journal of Mechanical and Electrical Engineering, 2025)
This study proposes a load frequency control (LFC) scheme that leverages virtual synchronous generator technology (VSG) to address the challenge of reduced power system inertia resulting from the integration of energy resources into the power grid. Firstly, a multi-area VSG-LFC model considering delay under the context of unreliable network transmission is developed. Secondly, this paper proposes an adaptive event-triggered mechanism (BAETM) based on the relative bandwidth occupation ratio, which dynamically regulates thresholds by considering the bandwidth state occupation ratio and system output state. The introduced mechanism effectively reduces data transmission and optimizes the utilization of limited network resources.